Closed reduction with external fixation and percutaneous screwing in talus neck fractures with severe soft tissue edema: A case report - Tekşan, Emre; Karadeniz, Sercan (Journal of Surgery and Medicine, 2021)
We herein report a patient with a Hawkins type 3 talus neck fracture because of a traffic accident. A 21-year-old male patient had excessive soft tissue edema in his ankle and suspicious COVID-19 findings in thorax chest computed tomography. Therefore, spinal anesthesia was administered to the patient for the operation, in addition to intravenous midazolam for sedation. Under external fixation, the ankle joint was distracted, and the fracture was reduced. The fracture was fixed percutaneously with two cannulated screws. The operation was completed with two one-centimeter incisions. There was no postoperative edema. The patient was discharged with an external fixator one day later. Percutaneous screwing after closed reduction with external fixation can be a successful method in patients with soft tissue edema.